Support programs for students at higher education institutions in South Africa: an appreciative inquiry study on managing alcohol abuse. (2nd January 2020) - Moagi, Miriam; Mulaudzi, Mavis; Van Der Wath, Annatjie
ABSTRACT: Objective: We explored stakeholders' perceptions of the alcohol abuse support programs for students in higher education institutions in South Africa. Methods: We used an appreciative inquiry approach to conduct group discussions with 22 participants (18 = women and 4 = men) working with student support programs at their institutions. Stakeholders included service providers and policy makers. Results: Following thematic analysis, we identified eight themes from two appreciative inquiry questions. Six themes emerged from the first question that assessed the positive aspects of support services, namely, counseling of students at risk, law enforcement, peer education, support groups and referral systems for students at risk, and continuous training for support staff. The second question assessed the challenges for support systems and included two themes, namely, easy access to alcohol and inadequate treatment programs. Conclusion: These findings informed the development of a comprehensive support program, which encompasses promotive, curative and rehabilitative services, to alleviate the burden of alcohol abuse among students at higher education institutions in South Africa.